The reconfiguration of accounting practices with the use of ChatGPT: Professionals' perceptions from the perspective of sociomateriality - Santos, Laura Romero dos; Behr, Ariel; Panizzon, Mateus (Contextus - Revista Contemporânea de Economia e Gestão, 2025)
Background: The accounting field is undergoing a transformation driven by technological advances, with emphasis on the use of artificial intelligence (AI), such as ChatGPT. This study examines how this technology can transform traditional interactions and optimize efficiency and accuracy in tax returns. Therefore, it is urgent to understand how ChatGPT, as a representative of innovations in AI, changes the flow of information and advice between accounting professionals and their clients. Purpose: This study aims to investigate the effects of the use of ChatGPT in the accountant-client communication process for preparing the Individual Income Tax Return. Method: The study is characterized as qualitative and exploratory, collecting data from accounting professionals through semi-structured interviews. The data were analyzed through content analysis with theory-driven coding, inspired by the sociomateriality approach. Results: The results reveal that the use of ChatGPT brought benefits, such as greater efficiency, reduction of errors and optimization of the time to perform some professional activities. Furthermore, there was a reconfiguration of accountants' tasks, who can now play a less repetitive role in some activities of the communication process. However, challenges also arise, such as the need to adapt and develop new digital skills. The results obtained can help accountants, other accounting professionals and researchers interested in the field of technology applied to accounting. Conclusions: The study revealed that the use of ChatGPT in the preparation of Individual Income Tax Return reconfigures operational tasks, organizational structures, and sociomaterial relations, implying a reformulation of accounting practice in the digital context. The analysis through the lens of sociomateriality offers an original perspective on the phenomenon, expanding an approach still incipient in accounting literature.